(551) A Course on Linear Programming and Extensions دورة في البرمجة الخطية وامتداداتها - الوليد ناصر الشافعي (معهد التخطيط القومي, 2026)
يعرض الجزء الثاني من دورة تدريبية متخصصة حول "البرمجة الخطية وتطبيقاتها"، مع التركيز بشكل أساسي على مشكلة النقل الكلاسيكية. يبدأ الملف بتحديد النموذج الرياضي للمشكلة، والذي يهدف إلى تقليل تكاليف نقل السلع من عدة مصادر إلى وجهات مختلفة مع الالتزام بقيود العرض والطلب. ويشرح الملف الخصائص الفريدة لهذا النظام، مثل "مثلثية الأساس"، التي تسمح بحل هذه المسائل بطرق أكثر كفاءة وسهولة من طريقة السمبلكس التقليدية، مستعرضاً خطوات عملية لإيجاد الحل الأساسي الأول الممكن واختبار أمثلته باستخدام المتغيرات المزدوجة (Dual Variables). ينتقل الملف في جزئه التطبيقي إلى تقديم خوارزميات برمجية مكتوبة بلغة فورتران (FORTRAN) لحل مشكلات النقل إلكترونياً، مع شرح مفصل لمفاهيم تقنية مثل "حلقة الأساس" (Basis Loop) وكيفية تحديث الحلول للوصول للمستوى الأمثل. كما يتناول الملف كيفية معالجة الحالات الخاصة والمعقدة، مثل زيادة العرض عن الطلب أو العكس عبر إضافة مصادر أو وجهات وهمية، والتعامل مع الطرق المستحيلة أو القيود على السعة. ويختتم الملف باستعراض مشكلة النقل المرتبطة بتكاليف الإنتاج والمصاريف غير المباشرة (Fixed Charge Transportation Problem)، موضحاً كيفية صياغتها كنموذج برمجة صحيحة للوصول إلى أفضل قرار اقتصادي يضمن أقل تكلفة إجمالية للتصنيع والنقل. The second part of a specialized training course on "Linear Programming and its Applications" focuses primarily on the classic transportation problem. The course begins by defining the mathematical model of the problem, which aims to minimize the costs of transporting goods from multiple sources to different destinations while adhering to supply and demand constraints. It explains the unique properties of this model, such as the "base triangularity," which allows for more efficient and straightforward solutions than the traditional simplex method. The course then presents practical steps for finding the first possible base solution and testing its optimality using dual variables.In its practical section, the course introduces programming algorithms written in FORTRAN for solving transportation problems electronically. It provides a detailed explanation of technical concepts such as the "base loop" and how to refine solutions to achieve optimum. The course also covers how to handle special and complex cases, such as supply exceeding demand or vice versa, by adding virtual sources or destinations, and how to deal with impossible routes or capacity constraints. The document concludes by reviewing the Fixed Charge Transportation Problem, which relates to production costs and indirect expenses, explaining how it can be formulated as a correct programming model to reach the best economic decision that ensures the lowest total cost of manufacturing and transportation.